Potential Effectiveness of Essential Oil as Natural Food Preservatives Compared with Chemical - Noor M. Witwit (Journal of Global Pharma Technology, 2018)
In this study, investigations were carried out to assess the efficiency of two plant essential oils; rosemary and thyme as natural food preservatives. The effect of the plant essential oils at concentrations of 1% and 2% was studied in the soft cheese against staphylococcus aureus and Escherichia coli at fridge temperature over a 5 day period. The essential oils performed well in the inhibition of Staphylococcus aureus and E. coli it is concluded that selected plant essential oils can act as potent inhibitors of both microorganisms in a food product, Thyme was found to be very active against E.coli in 2% and 1% (2.00, 2.66) respectively and S. aureus in 2% and 1% ( 7.66, 14.66) respectively followed by Rosemary in E.coli at 1% and 2% (4.33, 7.00) respectively also in S. aureus it effect in 2% more than 1% (5.00, 47.66) respectively. At the same time we compared their effect with weak acid as chemical preservatives in citric acid was found to be more effective than thyme and rosemary in 1% and 2% in E.coli and S. aureus (2.33, 1.00), (2.33, 1.33) respectively both essential oil and weak organic acid decreased growth of bacteria significantly when compared with control. Therefore, essential oils could be regarded as a source of food preservatives instead of chemical compounds.